Biofriendly molecular and protein release substrate with integrated piezoelectric motivation and anti-oxidative stress capabilities. Issue 18 (27th April 2021) - Zhang, Yi; Ma, Zequn; Zhang, Yihe; Li, Biao; Feng, Mengchun; Zhao, Yantao; An, Qi
Abstract : A multifunctional molecular delivery substrate was confirmed to promote molecular releases, molecules/proteins storage and ROS elimination in drug delivery. Abstract : Self-powered piezoelectrically active molecular or protein delivery devices have provoked great interest in recent years. However, electric fields used to promote delivery or healing may also induce the redox of water or oxygen to generate reactive oxygen species (ROS) and bring unintended oxidative pressure to the organism and harm biological functions. In addition, protein molecules are easily inactivated in the polymer reservoir matrix due to the pull of strong electrostatic effects. In this study, a multifunctional molecular delivery substrate was fabricated by integrating a piezoelectric–dielectric polymeric substrate, nanoscopic polyelectrolyte films and in-film deposited biomimetic porous CaP coating. The piezoelectric substrate promoted molecular release, and the mineralized coating effectively stored molecules or proteins and simultaneously eliminated ROS, reducing the oxidative stress response generated by oxidative pressure. The present work opens a new way for the development of multifunctional and biofriendly drug delivery devices.